The influence of different midsole hardness on knee joint loads during running - Michel, K. J.; Kleindienst, F. I.; Stacoff, A.; Krabbe, B.; Stüssi, E. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Midsole hardness influences abduction as well as external rotation moments in the knee joint. The hard shoe condition provokes significantly higher maximum abduction moments and higher maximum external rotation moments than the soft shoe condition. The results indicate that appropriate midsole hardness could have a positive effect on knee joint moments and subsequently on the reduction of overuse injuries.